2021
DOI: 10.3390/cancers13030470
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of the CHEK2 Germline Mutation and Its Impact on Clinicopathological Features, Treatment Responses, and Disease Course in Patients with Papillary Thyroid Carcinoma

Abstract: The CHEK2 gene is involved in the repair of damaged DNA. CHEK2 germline mutations impair this repair mechanism, causing genomic instability and increasing the risk of various cancers, including papillary thyroid carcinoma (PTC). Here, we asked whether CHEK2 germline mutations predict a worse clinical course for PTC. The study included 1547 unselected PTC patients (1358 women and 189 men) treated at a single center. The relationship between mutation status and clinicopathological characteristics, treatment resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
(67 reference statements)
1
3
0
Order By: Relevance
“…These studies, together with the three other Polish studies mentioned previously, found an increased I157T carrier frequency in papillary thyroid cancer patients compared to controls with odds ratios between 1,9 to 3,0 [7,8,14,16,17].…”
Section: Prevalence Of Germline Chek2 Mutations In Thyroid Cancer Pat...supporting
confidence: 68%
See 1 more Smart Citation
“…These studies, together with the three other Polish studies mentioned previously, found an increased I157T carrier frequency in papillary thyroid cancer patients compared to controls with odds ratios between 1,9 to 3,0 [7,8,14,16,17].…”
Section: Prevalence Of Germline Chek2 Mutations In Thyroid Cancer Pat...supporting
confidence: 68%
“…No statistically significant association was found between different individual truncating CHEK2 variants and thyroid cancer. When pooling the truncating mutations however, there was a statistically significant association (OR 4,54; 95%CI [1,40 – 14,68]; p = 0,0116), which was driven primarily by the IVS2 + 1G > A variant [ 14 ]. A case-control study of patients with non-anaplastic thyroid cancer in an Iranian population found no germline CHEK2 mutations in cases nor controls, though this probably reflects the low frequency of CHEK2 mutations in the Middle Eastern population [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…A CHEK2 p.Ile157Thr missense mutation was found in 12.3%, and CHEK2 truncating mutations (IVS2+1G>A, del5395, 1100delC) were found in 2.8%. While truncating mutations were more common in women and were associated with vascular invasion and intermediate or high initial risk in multivariate analysis, no significant differences were observed in patients with the p.Ile157Thr missense mutation ( 37 ).…”
Section: Susceptibility Genes Associated With Ns-fnmtcmentioning
confidence: 88%
“…A subsequent study in the same population confirmed that a CHEK2 truncating mutation (1100delC, IVS2+1G>A, del5395) was associated with odds ratio of 5.7 (p= 0.006), and a CHEK2 missense p.Ile157Thr mutation was associated with odds ratio of 2.8 (p= 0.0001) for PTC ( 104 ). In a more recent Polish series that included 1547 unselected PTC patients (1358 women and 189 men), CHEK2 mutations were found in 240 (15.5%) patients ( 37 ). A CHEK2 p.Ile157Thr missense mutation was found in 12.3%, and CHEK2 truncating mutations (IVS2+1G>A, del5395, 1100delC) were found in 2.8%.…”
Section: Susceptibility Genes Associated With Ns-fnmtcmentioning
confidence: 99%